UKESM1: Description and Evaluation of the U.K. Earth System Model. (21st December 2019) - Sellar, Alistair A.; Jones, Colin G.; Mulcahy, Jane P.; Tang, Yongming; Yool, Andrew; Wiltshire, Andy; O'Connor, Fiona M.; Stringer, Marc; Hill, Richard; Palmieri, Julien; Woodward, Stephanie; de Mora, Lee; et al.
Abstract: We document the development of the first version of the U.K. Earth System Model UKESM1. The model represents a major advance on its predecessor HadGEM2‐ES, with enhancements to all component models and new feedback mechanisms. These include a new core physical model with a well‐resolved stratosphere; terrestrial biogeochemistry with coupled carbon and nitrogen cycles and enhanced land management; tropospheric‐stratospheric chemistry allowing the holistic simulation of radiative forcing from ozone, methane, and nitrous oxide; two‐moment, five‐species, modal aerosol; and ocean biogeochemistry with two‐way coupling to the carbon cycle and atmospheric aerosols. The complexity of coupling between the ocean, land, and atmosphere physical climate and biogeochemical cycles in UKESM1 is unprecedented for an Earth system model. We describe in detail the process by which the coupled model was developed and tuned to achieve acceptable performance in key physical and Earth system quantities and discuss the challenges involved in mitigating biases in a model with complex connections between its components. Overall, the model performs well, with a stable pre‐industrial state and good agreement with observations in the latter period of its historical simulations. However, global mean surface temperature exhibits stronger‐than‐observed cooling from 1950 to 1970, followed by rapid warming from 1980 to 2014. Metrics from idealized simulations show a high climate sensitivity relative to previous generations of models: Equilibrium climate sensitivity is 5.4 K, transient climate response ranges from 2.68 to 2.85 K, and transient climate response to cumulative emissions is 2.49 to 2.66 K TtC −1 . Plain Language Summary: We describe the development and behavior of UKESM1, a novel climate model that includes improved representations of processes in the atmosphere, ocean, and on land. These processes are inter‐related: For example, dust is produced on the land and blown up into the atmosphere where it affects the amount of sunlight falling on Earth. Dust can also be dissolved in the ocean, where it affects marine life. This in turn changes both the amount of carbon dioxide absorbed by the ocean and the material emitted from the surface into the atmosphere, which has an affect on the formation of clouds. UKESM1 includes many processes and interactions such as these, giving it a high level of complexity. Ensuring realistic process behavior is a major challenge in the development of our model, and we have carefully tested this. UKESM1 performs well, correctly exhibiting stable results from a continuous pre‐industrial simulation (used to provide a reference for future experiments) and showing good agreement with observations toward the end of its historical simulations. Results for some properties—including the degree to which average surface temperature changes with increased amounts of carbon dioxide in the atmosphere—are examined in detail. Key Points: UKESM1 represents a major advance over its predecessor HadGEM2‐ES, both in the complexity of its components and its internal coupling The complex coupling presents challenges to the model development; we document the tuning process employed to obtain acceptable performance UKESM1 performs well, having a stable pre‐industrial state and showing good agreement with observations in a wide variety of contexts